Pergeseran Pemosisian Subjek Kelas Bawah dalam Tiga Film Bong Joon-Ho - Pinem, Agnes Rosalina (Universitas Brawijaya, 2022)
Bong Joon-ho is a South Korean film director and the last three film he directed were Snowpiercer, Okja and Parasite. Those films had the same theme which is social class inequality in the capitalist system. Researcher used Norman Fairclough's critical discourse analysis to find out the representation of the lower class in the three films and then used Michel Foucault's subject position theory to find the shifting position of lower- class subjects in three Bong Joon-Ho films. The result, this study found out that there were 4 shifts in the positioning of lower class subjects represented in those three films. In these films, capitalists are portrayed as the winning party but the way Bong Joon-ho positions the relationship between the lower class and the upper class was different. In these films, Bong Joon-ho conveys his thoughts and concern about the impact of the capitalist system to the society. Through his last film Parasite, Bong Joon-ho wanted to show that both the lower class and the upper class could become a victim in the capitalist system. These three films show that there is no alternative to the capitalist system and that in the end people just have to respect each another.